LINSEC - The software for modeling and simulation of grain drying system - Magalhães Valente, Domingos (2012)
Considering the importance of mathematical models in the development and analysis of grain drying systems, and understanding the need to develop interfaces that will improve the accessibility of these models, this work aimed to: a) implement the Thompson model to simulate grain drying at high temperatures; b) develop an appropriate language to generate drying models; and c) develop a graphical interface with the goal of facilitating user understanding. Thus the computational program LINSEC that was created using the programming language Visual Basic 6.0. LINSEC was highly effective for the modeling and simulation of drying systems and in providing simulated values close to reality. LINSEC is highly flexible and user-friendly during the modeling of several types of dryers.